2020
DOI: 10.1103/physrevb.101.054436
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of magnon spin transport in a magnetic gate transistor

Abstract: We demonstrate a modulation of up to 18% in the magnon spin transport in a magnetic insulator (Y3Fe5O12, YIG) using a common ferromagnetic metal (permalloy, Py) as a magnetic control gate. A Py electrode, placed between two Pt injector and detector electrodes, acts as a magnetic gate in our prototypical magnon transistor device. By manipulating the magnetization direction of Py with respect to that of YIG, the transmission of magnons through the Py|YIG interface can be controlled, resulting in a modulation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
(29 reference statements)
1
19
3
1
Order By: Relevance
“…In this regard, all-electrical magnon transport experiments already showed that they are beneficial to qualitatively and quantitatively investigate charge-to-spin current conversion processes in magnetically ordered conductors. [69,74,95,101,104] As a next step, we have to describe the transfer of spin momentum at the interface between the NM and the MOI. A detailed theoretical description is presented in the study by Bender et al [105] including heat transport across the NM/MOI interface.…”
Section: Electrical Injection and Detection Of Magnonsmentioning
confidence: 99%
“…In this regard, all-electrical magnon transport experiments already showed that they are beneficial to qualitatively and quantitatively investigate charge-to-spin current conversion processes in magnetically ordered conductors. [69,74,95,101,104] As a next step, we have to describe the transfer of spin momentum at the interface between the NM and the MOI. A detailed theoretical description is presented in the study by Bender et al [105] including heat transport across the NM/MOI interface.…”
Section: Electrical Injection and Detection Of Magnonsmentioning
confidence: 99%
“…58 The interaction between triplet Cooper pairs and magnons constitutes a fascinating research direction. Magnon-based devices have been explored as interconnecting elements in spin logic architectures, and achieving magnon modulation via the magnetic field 113 or electrical gating [114][115][116] is important for implementing magnonic logic functionalities. A recent study demonstrates that spin wave transmission within a Py layer between injector and detector antennas is modulated up to 40% by opening and closing a spin dissipation channel consisting of triplet correlations in a nearby Nb layer, as shown in Fig.…”
Section: Challenges and Prospects Of Superconducting Spintronicsmentioning
confidence: 99%
“…Note that, as proposed by K. S. Das et al [17], our device can be also used as a spin transistor, whereby the absorber constitutes a magnetic gate allowing a significant modulation of the spin signal. The 40% variations observed here reveal indeed relatively large with respect to the state of the art [18,19].…”
mentioning
confidence: 76%